Vector Autoregression Analysis of The Relationship Between Inflation Rate, Interest Rate, and Exchange Rate To The Jakarta Islamic Index - Qurrota A'yun, Ajeng; Fatwa, Nur (UI Scholars Hub, 2022)
ABSTRACT The Indonesian Sharia Capital Market is an interesting thing to study because based on the 2019 Global Islamic Finance Report (GIFR) report, Indonesia is ranked first in the Global Sharia Financial Market. The Jakarta Islamic Index (JII) is the sharia stock index that was first launched on the Indonesian capital market on July 3, 2000 and only consisted of the 30 most liquid Islamic shares listed on the Indonesia Stock Exchange. This study will try to uncover how the relationship between macroeconomic variables in Indonesia by using Vector Autoregression (VAR) analysis and using monthly secondary data from 2012-2019. VAR analysis which has advantages including multivariate, free from spurious endogeneity and exogeneity variables and can detect relationships between variables in the equation system. The results of this study indicate that the JII of the previous period and the BI Rate have a positive influence on JII, while inflation and the Rupiah-US Dollar Exchange rate have a negative relationship with JII. The implication of the results of this study is to strengthen the rupiah price which greatly affects JII. Keywords: Shariah stock, JII, Macroeconomics, VAR.